2021
DOI: 10.1177/03635465211022798
|View full text |Cite
|
Sign up to set email alerts
|

Image-Guided Intra-articular Hip Injections and Risk of Infection After Hip Arthroscopy

Abstract: Background: Although intra-articular injections are important in the management of patients who may later undergo hip arthroscopy, conflicting data are available regarding the safety of such injections when administered within 3 months of surgery. Furthermore, despite the increasing use of image-guided intra-articular hip injections, it is unknown whether the type of imaging modality used is associated with infection after hip arthroscopy. Purpose: To assess the risk of infection associated with image-guided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Because the International Classification of Diseases (ICD)-9 codes do not provide laterality, we could not confirm the laterality of ONFH. However, this bias would result in the true rates of ONFH being even lower than what was reported and it would apply to both groups, and ICD-9 codes have been used extensively to study the risks associated with intraarticular injections in orthopaedic surgery 31,32,[45][46][47][48][49][50] . As the primary injectate is frequently the only medication that is billed, we were unable to analyze the role of any concurrent anesthetic.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Because the International Classification of Diseases (ICD)-9 codes do not provide laterality, we could not confirm the laterality of ONFH. However, this bias would result in the true rates of ONFH being even lower than what was reported and it would apply to both groups, and ICD-9 codes have been used extensively to study the risks associated with intraarticular injections in orthopaedic surgery 31,32,[45][46][47][48][49][50] . As the primary injectate is frequently the only medication that is billed, we were unable to analyze the role of any concurrent anesthetic.…”
Section: Discussionmentioning
confidence: 97%
“…Similar to prior work 31,32 , we first identified all patients who received an intra-articular HAI or CSI of the hip using Current Procedural Terminology ([CPT] 20610/20611) and Healthcare Common Procedure Coding System codes (Appendix Table I). Patients with a history of osteonecrosis or those who underwent both types of injections were excluded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike other acute inflammatory joint diseases, e.g., rheumatoid arthritis (RA), gouty arthritis (GA), or psoriatic arthritis (PA), the development of OA is a gradual and slow process lasting decades. Injection-based therapies require repeated intra-articular administration, which may increase tissue damage and risk of infection [ 56 ]. The hydrogel-inspired method effectively prolong the time for the drug to take effect; however, the excessive rigidity of some hydrogels may impair the superlubricity between articular cartilage surfaces [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In an early study, Wang et al raised concern about injections increasing the risk of infection after hip arthroscopy 9 ; however, in a follow-up study, Byrd et al found no infections among 500 patients undergoing ultrasound-guided hip injections in the 3 months before hip arthroscopy 10 . In 2021, Varady et al published a retrospective cohort study of 17,987 patients further evaluating the infection risk of ultrasound and fluoroscopy-guided injections prior to hip arthroscopy 11 . A total of 12.7% of patients received an image-guided hip injection within the year preceding the surgical procedure.…”
Section: Hipmentioning
confidence: 99%